The Interactive Role of Organizational Culture in the Relationship Between Organizational Commitment and Outstanding Performance : An Analytical Study of the Opinions of A Sample of Employees in the Diwan of the Directorate of Education in Dhi Qar - Kareem Jaber Dhahi (International Journal of Economics and Management Sciences, 2025)
This study sought to achieve a set of objectives, the most important of which is preparing atheoretical framework for the research variables through which it clarifies the role of interactiveorganisational culture and its impact on the relationship between organisational commitment andoutstanding performance, building a hypothetical model between the study variables andexplaining the effect between these variables, identifying the impact of organisational culturedimensions on exceptional performance, determining the effect of organizational commitment onoutstanding performance. The study used statistical tools to analyse and process data andinformation, including the (SPSS) program and the questionnaire. The study community wasadopted, represented by (Dhi Qar Directorate Office). The study sample was all employees in theDhi Qar Education Directorate Office, where the sample numbers were (1200) and (290) weredistributed using the Morcan model. The total number of valid questionnaires for analysis was(257) questionnaires.